Field efficacy of flubendiamide 20WG against rice leaffolder, Cnaphalocrocis medinalis (Guenee) and yellow stem borer, Scirpophaga incertulas (Walker) in basmati rice - Jaglan, Maha Singh; Chaudhary, Om Pal (Journal of Cereal Research, 2021)
Rice leaffolder, Cnaphalocrocis medinalis (Guenee) and yellow stem borer, Scirpophaga incertulas (Walker) are the two dominant species among the rice pests and cause considerable damage in India. Various strategies have been employed for managing these pests and insecticides as chemical control factors are the first line of defense but it has become difficult to manage these pests due to the development of resistance. Therefore, identification of new molecules with selective properties, novel mode of action, low toxicity to non-targets and environmental safety is required with a view of sustainable pest management. In this direction, a new molecule i.e., flubendiamide 20 WG was evaluated in the field conditions at multi-locations to access its efficacy against rice leaffolder and yellow stem borer during Kharif, 2020 at farmers, field in basmati rice. Foliar spray of flubendiamide 20 WG @ 25 g a.i. ha-1economic threshold effectively reduced the infestation of rice leaffolder and yellow stem borer. Foliar application of flubendiamide 20 WG (25g a.i. ha-1) did not cause any phytotoxicity symptoms on the crop. Average grain yield (37.14 q ha-1) was observed in application of flubendiamide 20 WG at 25 gm a.i. ha-1 as compared to control (32.24 q ha-1). Â